The critical movement around the poetry of Omar bin Abi Rabiah - Atiyeh, Aya Mohammad (Journal of Arabic Language Sciences and Literature, 2022)
This study was concerned with tracking the critical movement around the poetry of Omar bin Abi Rabiah and the development of the critical approach starting from the Umayyad era until the fifth century AH.The researcher monitored the dynamic changes in the monetary movement during the two periods of psychological transition, which contributed to the formation of the poetic environment of Omar bin Abi Rabiah. Based on that, the researcher stopped at the two stages of poetic formation represented in the periods of youth and old age. Also, this study concluded that the poetic movement of Omar bin Abi Rabia was affected by the temporal trajectory of his poetry, as it revived in the youth period after achieving harmony between the poet’s psychological inclinations and the requirements of the environment at that time.Whereas, due to the imbalance of the harmony, it relapsed in the aging period..
Keywords: Omar bin Abi Rabiah; Arabic poetry; criticism